ANTROPOLOGI KULINER EKONOMI MORAL PEMBUAT SERABI SEBAGAI WUJUD BUDAYA DI DESA KALIBELUK - Dhafin, Fausta (Bapelitbang Kabupaten Batang, 2024)
ABSTRACT This research aims to examine how Kalibeluk Serabi makers carry out economic activities that are inversely proportional to conventional economic laws which are fully oriented towards profit and create healthy competition for the market in line with these laws. Instead of that, the Serabi makers in Kalibeluk run this business not completely oriented towards profit and competition between each other. The serabi makers are actually empowered by a social network consisting of those who would otherwise act as competitors; they support each other, and are supported by Islamic and Javanese culture. In line with Islamic and Javanese culture, serabi makers adhere to the principles of harmony, patience and tenacity. This patience and tenacity is a challenge in itself, especially for the new generation who see the productive activity of making serabis through the lens of materials. This is because patience, which is a value in life for the traditional art of selling, is not a profitable thing. This research then found the values ​​that accompanied the activities of the Kalibeluk Serabi makers which were reviewed through the perspective of James Coleman's rational choice theory. These values ​​are always upheld, some of which are cultural values, family values, moral values, traditional values ​​and independence values. Keywords: Serabi maker, productive activity, social process, rational choice, moral economy, rational economy, adaptive strategy.